Cecidomyiidae (Diptera) in the State of Santa Catarina, Brazil - Flor, Ismael C.; Maia, Valéria C. (Entomological Communications, 2022)
The first checklist of gall midges (Diptera: Cecidomyiidae) in the state of Santa Catarina (SC) is organized based on literature review. Species distribution, discussion regarding endemism, and a list of host plants in the state are provided for the first time. We compare the composition of cecidomyiid species with other states of Brazil. Twenty-three species of gall midges occur in SC, all gall-inducers. They are distributed in 14 genera, being Lopesia Rübsaamen, 1908 and Bruggmannia Tavares, 1906 the best represented. The most speciose genera of Cecidomyiidae in SC are among the most speciose in Brazil, so this result matches the Brazilian pattern. Cecidomyiids are associated with 18 host plant species distributed in 12 families. Although SC comprises a low percentage of the Brazilian fauna of Cecidomyiidae (8.7%), two species are known only from the state. The Sorensen`s index showed that the fauna of SC and São Paulo (SP) are the most similar to each other. The similarity of gall-inducing insects can be related to the host plant composition and phytogeographic domain.